Penerapan Model Pembelajaran Investigasi Kelompok Bebantuan SPSS Untuk Meningkatkan Hasil Belajar Biostatistik Mahasiswa PSIK - Riki Musriandi; Cut Delsie Hasrina (Jurnal Dedikasi Pendidikan, 2019)
This study aims to describe the learning outcomes of Biostatistics of Nursing Students Abulyatama University by applying group investigation learning model assisted by the SPPS. This research is an experimental research with a quasi-experimental approach or better known as a quasi-experiment. The subject of this research is the Nursing Students of Abulyatama University Academic Year 2017/2018. Whereas the sample in this study are the Nursing students who took Biostatistics in the Even Semester of Academic Year 2017/2018. The obtained results showed that the average learning outcomes of the Nursing students before getting treatment was still very low. While the average score of Biostatistics of the Nursing students are quite good after applying Group Investigation Learning model assisted by SPSS. As for improvement of Biostatistics’ learning outcome of the Nursing students with the application Group Investigation Leaning Model assisted by SPSS is very significant. The application of the Group Investigation Leaning Model assisted by SPPS received a good response from the students of Nursing of Abulyatama University.